To thank or not to thank: Understanding the differences between gratitude and indebtedness after receiving a favor through emotion appraisals, motivations and behaviors - NAI, Ze Ling (Institutional Knowledge at Singapore Management University, 2019)
Objective: This study aimed to distinguish between daily experiences of gratitude and indebtedness through three stages - emotional appraisals, motivations to reciprocate and behavioural tendencies. Through these three stages, I aimed to gain a better insight into the emotional process involved before and after receiving favours. Method: 196 participants were recruited from Singapore Management University to take part in a 14-day diary study. Every two days, participants were asked to report a favour they received over the past two days and evaluate the favour based on their appraisals of the experience. They were also asked to report their motivation to reciprocate each favour received. Upon completing the diary study, participants attended a follow-up session where were asked to report their behavioural tendencies over the past week. Results: Gratitude and indebtedness were associated with varying extents with different benefit appraisals. For instance, gratitude was positively associated with perceived benevolence and indebtedness with perceived expectations of repayment. Gratitude was also found to motivated reciprocity via the desire to affiliate, while indebtedness motivated reciprocity through the desire to adhere to the norm of reciprocity. Finally, gratitude was associated with increased reports of affiliative behaviours while indebtedness was associated with the likelihood of repaying the favour. The theoretical implications, practical implications, and future directions of these findings were discussed.